Analisis Daya Saing Usahatani Tanaman Hias Philodendron Selloum di Kecamatan Karang Tengah Kota Tangerang - Saleh, Khaerul -; Aliudin, Aliudin; Meissyanna, Meissyanna (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2024)
This study aimed to determine the competitiveness of comparative and competitive advantage of philodendron selloum as ornamental plants, and to determine the impact of government policies on input or output prices on philodendron selloum farmers. Descriptive quantitive method was used in this research. The study was conducted at Karang Tengah Sub-district Tangerang City. Primary data sources were obtained by using an interview and questionnaire list with 33 farmers as sample data in this study. Secondary data were obtained from notes and documentation. There were three methods of analysis carried out in this study. Policy Analysis Matrix (PAM) was used as research analysis to find out about financial and economic advantages, the value of both comparative and competitive advantage, and the impact of government policies on inputs-outputs toward economy activity. The result of this study revealed that philodendron selloum farming in this sub-district have both comparative and competitive advantage. It can be seen in the production’s efficiency with PCR value of 0,59 and DRCR value of 0,39. Meanwhile, government policies related to output (NPCO), inputs (NPCO), and input-output (EPC) has not been able to run effectively and considered to have not been able to protect philodendron selloum farmers (producer).